Type 1 Monteggia Equivalent Fracture with Ipsilateral Distal Radius Fracture: A Case Report - Gokceoglu YS; Ozger EY (Malaysian Orthopaedic Journal)
In this case report, we present a 13-years-old patient who sustained a Monteggia equivalent fracture along with an ipsilateral distal radius fracture following a fall on the elbow. Comminuted ulnar fracture was treated with open reduction and internal fixation with a bridging plate. After restoring the ulnar length, the radial neck fracture was successfully reduced. The distal radius fracture was managed conservatively. Our literature review shows that, the patient is one of the comparatively older patients treated with open reduction and internal fixation in this area and that a successful outcome was achieved with early mobilisation. This case underscores the need for further studies to determine the optimal treatment strategy in such cases.